All type II classic MADS‐box genes in the lycophyte Selaginella moellendorffii are broadly yet discretely expressed in vegetative and reproductive tissues. Issue 3 (5th March 2021) - Ambrose, Barbara A.; Smalls, Tynisha L.; Zumajo‐Cardona, Cecilia
Abstract: The MADS‐box genes constitute a large transcription factor family that appear to have evolved by duplication and diversification of function. Two types of MADS‐box genes are distinguished throughout eukaryotes, types I and II. Type II classic MADS‐box genes, also known as MIKC‐type, are key developmental regulators in flowering plants and are particularly well‐studied for their role in floral organ specification. However, very little is known about the role that these genes might play outside of the flowering plants. We investigated the evolution of type II classic MADS‐box genes across land plants by performing a maximum likelihood analysis with a particular focus on lycophytes. Here, we present the expression patterns of all three type II classic MADS‐box homologs throughout plant development in the lycophyte Selaginella moellendorffii : SmMADS1, SmMADS3, and SmMADS6 . We used scanning electron microscopy and histological analyses to define stages of sporangia development in S. moellendorffii . We performed phylogenetic analyses of this gene lineage across land plants and found that lycophyte sequences appeared before the multiple duplication events that gave rise to the major MADS‐box gene lineages in seed plants. Our expression analyses by in situ hybridization show that all type II classic MADS‐box genes in S. moellendorffii have broad but distinct patterns of expression in vegetative and reproductive tissues, where SmMADS1 and SmMADS6 only differ during late sporangia development. The broad expression during S. moellendorffii development suggests that MADS‐box genes have undergone neofunctionalization and subfunctionalization after duplication events in seed plants. Abstract : There are only three Type II classic MADS‐box genes present in the genome of the lycophyte, Selaginella moellendorffii, and all are broadly yet discretely expressed in vegetative and reproductive structures. Research Highlight: The evolution of MADS‐box genes shows multiple seed plant‐specific duplications and all lycophyte homologs are preduplication. Expression analyses in Selaginella moellendorffii suggest that these genes have undergone neo‐ and subfunctionalization in seed plants.